2000
DOI: 10.1007/s00585-000-0945-6
|View full text |Cite
|
Sign up to set email alerts
|

Annual and semiannual variations in the ionospheric F2-layer: II. Physical discussion

Abstract: Abstract. The companion paper by Zou et al. shows that the annual and semiannual variations in the peak F2-layer electron density (NmF2) at midlatitudes can be reproduced by a coupled thermosphere-ionosphere computational model (CTIP), without recourse to external in¯uences such as the solar wind, or waves and tides originating in the lower atmosphere. The present work discusses the physics in greater detail. It shows that noon NmF2 is closely related to the ambient atomic/molecular concentration ratio, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
183
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(203 citation statements)
references
References 15 publications
17
183
1
2
Order By: Relevance
“…[24] Our analysis has shown that seasonal differences in daytime N m F 2 solar activity variations are due to the different roles which neutral composition (O, O 2 , N 2 ) and temperature play in summer and in winter, and the observed seasonal difference in N m F 2 is not simply reduced to seasonal O/N 2 variations [e.g., Millward et al, 1996;Rishbeth et al, 2000;Richards, 2001;Yu et al, 2004].…”
Section: Seasonal Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[24] Our analysis has shown that seasonal differences in daytime N m F 2 solar activity variations are due to the different roles which neutral composition (O, O 2 , N 2 ) and temperature play in summer and in winter, and the observed seasonal difference in N m F 2 is not simply reduced to seasonal O/N 2 variations [e.g., Millward et al, 1996;Rishbeth et al, 2000;Richards, 2001;Yu et al, 2004].…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…[2] Seasonal and December anomalies in N m F 2 variations have been studied since the beginning of ionospheric observations [Appleton and Naismith, 1935;Seaton and Berkner, 1939;Yonezawa and Arima, 1959]; however, the mechanisms of their formation are still discussed in publications [Richards et al, 1994c;Rishbeth et al, 2000;Richards, 2001;Kawamura et al, 2002;Yu et al, 2004;Pavlov and Pavlova, 2005;Rishbeth and Müller-Wodarg, 2006;Zhao et al, 2007]. Among different explanations proposed during the decades of the problem analysis [see Rishbeth, 1998], the suggestion by Rishbeth and Setty [1961] that F 2 layer seasonal anomaly is due to neutral composition variation may be considered as generally accepted [Rishbeth et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The zonal mean TECs maximize around the equinoxes (days 90 and 300), and minimize around the solstices (days 30 and 210). This variation in zonal mean TEC amplitude corresponds to the known semiannual variation in the ionosphere that has been connected to seasonal variations in the O/N 2 ratio (Rishbeth et al 2000). The twin bands of the EIAs on either side of the magnetic equator are not distinct in the case of the zonal mean TECs, likely due to the diurnal nature of the equatorial fountain mechanism (Appleton 1946).…”
Section: Methodsmentioning
confidence: 77%
“…According to Rishbeth et al (2000) the electron density variation (or anomaly) of the F2 layer can be divided into 3 types: seasonal variation (or winter variation), semiannual variation and annual or non-seasonal variation. Seasonal variation refers to the phenomenon that the NmF2, which is the maximum electron density in the F2 layer, is larger in winter than in summer usually in the day time in the middle latitudes.…”
Section: Introductionmentioning
confidence: 99%